Assessing the laboratory efficacy of cypermethrin, deltamethrin, and gel baits against the German cockroach (Blattella germanica L.) - Krešimir Šimunac; Luka Mustapić; Renata Bažok; Petra Mustapić; Martina Kadoić Balaško (Journal of Central European Agriculture)
The German cockroach (Blattella germanica L.) is a significant pest in urban areas and is known for its ability to resist insecticides. Today, resistance to insecticides makes the control of agriculturally, economically and medically important insect pests considerably more difficult. This study represents the first investigation on the resistance of B. germanica in Croatia. After control failures with pyrethroid insecticides, a population of B. germanica was collected from a public place in Zagreb, Croatia. A susceptible population, which was kept under laboratory conditions for over 20 years without contact with insecticides, was obtained from Austria. The experiment was conducted on adults according to the IRAC protocol (No. 037). Active ingredients (AIs) commonly used to control this pest were tested: cypermethrin and deltamethrin as solutions and imidacloprid and chlorfenapyr in the form of gel baits. The results for cypermethrin and deltamethrin showed little to no efficacy in the site population after 72 hours, even at a dose 40 times higher than the dose that achieved full efficacy in the laboratory population. The efficacy of two gel baits with chlorfenapyr and imidacloprid after 72 hours was 40% and 68% higher in the laboratory population than in the site population, respectively. Neither the insecticides nor the gel baits showed sufficient efficacy in the site population of B. germanica. Considering these findings and observed resistance, it is essential to implement an anti-resistance strategy including the use of insecticides from various chemical groups, mechanical, biological and biotechnological measures as well as accompanying measures to reduce pest populations.